Thermotolerance and Antibacterial Properties of MgO-Triclosan Nanocomposites. (2015) - Cui, Hongmei; Wu, Xiaofeng; Zhang, Donghai; Zhang, Jingkun; Xiao, Hong; Chen, Yunfa
Abstract: Antibacterial MgO-Triclosan nanocomposites was prepared by a facile adsorption process using nano-MgO as adsorbent in a triclosan ethanol solution. Adsorption experiments showed that as-synthesized MgO nanoparticles possess high adsorptive capability towards triclosan. TG and FTIR analysis showed that the MgO-Triclosan nanocomposites performed good thermotolerance. Antibacterial tests showed that it still retained most of its active component, and exhibits high antimicrobial activity even after heat treatment for 30 min at 250 °C.